Development of a food formula with CBD to mitigate the symptoms of covid-19. - Vargas Upegui, Alejandro Mauricio
Exploring biocompounds present in all types of kingdoms of nature can help us mitigate the symptoms presented by the COVID-19 virus infection that caused the 2020 pandemic and cost millions of lives worldwide. Objective: This research seeks the development of a food formula from biocompounds, which allows combating the symptoms of COVID-19. Materials and methods: through a bibliographic search of articles with in vitro, in silico and clinical studies, an estimation of Absorption, Distribution, Metabolism and Excretion (ADME) parameters, studies in cellular models and tools such as molecular docking against 11 protein targets. viral, the selection of the most optimal biocompounds was possible through an Artificial Neural Network. Subsequently, a bibliographic search was carried out to validate compliance with the parametersof national legislation, in its use for food formulas, phytotherapeutic products and its safety in foods approved by the Food and Drug Administration (FDA), resulting in the identification of 3 selected compounds (CBD, Eicosapentaenoic Acid and Quercetin). Cannabidiol (CBD) was selected to carry out cell viability and antiviral activity tests against COVID-19 given that this compound complies with national legislation for its implementation and is approved by the FDA in a human medicine, for rare and severe forms of epilepsy. Results and Conclusion: These in vitro assays resulted in noncytotoxicity and an antiviral activity of 92% at a CBD concentration of 6μM. The CBD was subsequently implemented in a powdered food formulation developed by the research and development unit of the company ALSEC Productos Secos S.A.S., which allows mitigating the symptoms of COVID-19 and has an antiviral activity superior to that of the active ingredient alone.